CIRFF 2015 - Plénière pour et par les femmes autochtones avec Suzy Basile (2015)
Communication de Suzy Basile, à la Plénière soulignant les 40 ans de Femmes Autochtones au Québec (FAQ), au Congrès CIRFF2015, mardi 25 août 2015, UQAM. «Penser Créer Agir - Recherche et co-construction des connaissances avec, pour et par les femmes autochtones.» 7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) http://cirff2015.uqam.ca/ 24 au 28 août 2015, Université du Québec à Montréal.
Keywords: 1800-1899; amériques; approches et analyses; canada; féminisme autochtone; féminisme décolonial; genre; identités LGBTQIA2+; loi sur les indiens; premières nations; périodes historiques; québec; recherche participative; régions géographiques; sujet de recherche; thématiques

Whispers of the Unspeakable: New York and Montreal Newspaper Coverage of the Oscar Wilde Trials in 1895 - Robinson, Greg (Journal of Transnational American Studies, 2015)
Greg Robinson’s article “Whispers of the Unspeakable: New York and Montreal Newspaper Coverage of the Oscar Wilde Trials in 1895,” originally published in 2010 in the French-language journal Rue des Beaux Arts, no. 24 (2010), is here republished and—with much gratitude—translated (for the original text, please see http://www.oscholars.com/RBA/twenty-four/24.7/Articles.htm). Robinson’s transnational study focuses on how reading the specific language of newspaper reports of the Oscar Wilde case, literally from a distance, from places less emotionally attached to and nationally distinct from the scandal’s epicenter in London, England, provides insight into “the state of everyday public knowledge and discussion of (homo)sexuality, at least west of the Atlantic”; thus Robinson’s fascinating research, which involves numerous newspapers—from the elite New York Times to the New York Herald, from the Montreal Daily Star to the French-language papers of Quebec—concludes that the popular press, read transnationally, offers key insights into the developing attitudes toward and levels of interest in the newly forming identity of the “homosexual” across societies.
En accès libre : https://escholarship.org/uc/item/74n7c590
Keywords: 1800-1899; amériques; analyse comparée; analyse de discours; approches et analyses; cours; discipline; discours dominant; discours médiatique; his4860; histoire; homophobie; hétérosexisme; montréal; new york; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques